2017
DOI: 10.24171/j.phrp.2017.8.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Sex-based Association between Depression and Metabolic Syndrome in Korean Middle-aged and Older Adults

Abstract: ObjectivesThis study aimed to identify the sex-based association between depression and the development of metabolic syndrome (Mets) among middle-aged and older Korean adults.MethodsA cross-sectional design was used for the secondary analysis of the 2010–2014 Korean National Health and Nutrition Examination Survey. Data from 1,938 men and 2,404 women were analyzed. Mets was defined in accordance with the criteria used for clinical diagnosis. Depression was assessed with a question about having clinical depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
14
0
2
Order By: Relevance
“…Similarly, study conducted in Korea with middle-aged individuals aged 40-64 years found high prevalence among women with 11.7%, compared to 4.1% in men. 39 These findings may be similar to what was found in disease prospective cohort among the Dutch population, where depression was significantly associated with higher WC and triglyceride levels during a 6-year follow-up. 40 In this context these results may imply that older age may be associated with an increased response to stress and cortisol levels, more frequently among women than men.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, study conducted in Korea with middle-aged individuals aged 40-64 years found high prevalence among women with 11.7%, compared to 4.1% in men. 39 These findings may be similar to what was found in disease prospective cohort among the Dutch population, where depression was significantly associated with higher WC and triglyceride levels during a 6-year follow-up. 40 In this context these results may imply that older age may be associated with an increased response to stress and cortisol levels, more frequently among women than men.…”
Section: Discussionsupporting
confidence: 88%
“… 40 In this context these results may imply that older age may be associated with an increased response to stress and cortisol levels, more frequently among women than men. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Among cohort studies, the highest and lowest sample sizes were for the studies by Dregan [ 34 ] ( n = 124,445) and Viinamaki [ 35 ] ( n = 223), respectively. Results were reported by gender in four studies [ 13 , 25 , 36 , 37 ] and by type of depression (typical vs. atypical) in one study [ 38 ]; these studies were included in the analysis as two separate studies. In addition, three cross-sectional studies reported their results by gender; these were included in the analysis as three separate studies [ 7 , 34 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of depression varies, and is higher among woman. Its prevalence in Korean middle-aged and older adults was previously reported to be 4.1% in men and 11.7% in women [ 7 ]. Another study on an older Chinese population suggested that the risk of depression was 1.98-fold higher in women than in men [ 8 ].…”
Section: Introductionmentioning
confidence: 99%